KUALITAS PELAYANAN ADMINISTRASI DI DESA SABAH BALAU - Apriyani, Yuyun (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
One of the main tasks that is very crucial for the government is to guarantee quality public services for citizens. Therefore, government agencies are often referred to as